2000
DOI: 10.1007/s11746-000-0106-5
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of farmed and wild salmon (Salmo salar) by a combined use of compositional and isotopic analyses

Abstract: Gas chromatography, isotope ratio mass spectrometry, and high-resolution 2 H site-specific natural isotope fractionation/nuclear magnetic resonance spectroscopy have been used to study the different kinds of fish oils and lipids extracted from muscle of wild and farmed salmon (Norway, Scotland). A statistical analysis of the fatty acid compositions, overall 2 H and 13 C isotope ratios, and molar fractions of the isotopomeric deuterium clusters was carried out to select the most efficient variables for distingu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(46 citation statements)
references
References 22 publications
1
45
0
Order By: Relevance
“…Salmon produced using diets containing raw materials with high levels of marine FO currently provide a rich source of the n-3 HUFA, EPA, and DHA that are relatively cheap and highly nutritious (21,22). However, the growth in aquaculture required to augment dwindling seafood stocks can be sustained only if alternatives to marine FO can be found (5,7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Salmon produced using diets containing raw materials with high levels of marine FO currently provide a rich source of the n-3 HUFA, EPA, and DHA that are relatively cheap and highly nutritious (21,22). However, the growth in aquaculture required to augment dwindling seafood stocks can be sustained only if alternatives to marine FO can be found (5,7).…”
Section: Discussionmentioning
confidence: 99%
“…Atlantic salmon fed diets containing raw materials of predominantly marine origin are of high nutritional quality, being rich in EPA and DHA and with an n-3/n-6 ratio of around 4:1 (21,22). Recent studies have shown that salmon cultured using diets in which >50% of added FO has been replaced with vegetable oil show significant reductions in flesh EPA and DHA concentrations (14)(15)(16)(17).…”
mentioning
confidence: 99%
“…In fish, LC-PUFAs are mainly located in the sn-2 position of the TAG, while saturated fatty acids and monounsaturated fatty acids are located primarily in the sn-1 and sn-3 position (Ackman, 1980). Saturated fatty acids (14:0, 16:0 and 18:0) were preferentially esterified in both sn-1 and sn-3 positions, whereas LC-PUFAs were preferentially located in the sn-2 position (Aursand et al, 1995;Ando et al, 1996;Aubourg et al, 1996;Nwosu and Boyd, 1997;Aursand et al, 2000). It is interesting that in the TAG lipids of marine mammals (whale, seal), the sn-2 position is more enriched in saturated fatty acids and LC-PUFA is more located in sn-1 and sn-3 position (Brockerhoff et al, 1967;Ackman, 1980).…”
Section: Lipids From Marine Sources: Structure and Compositionmentioning
confidence: 99%
“…For instance, it has been employed to detect the adulteration of honey (Chesson et al, 2011;Simsek et al, 2012), differentiate farm and wild salmon species (Aursand et al, 2000) and test the authenticity of vegetable oils namely sunflower oil, corn oil, groundnut oil, palm oil, rapeseed oil and olive oil (Kelly et al, 1997;Bianchi et al, 1993). However, studies dealing with the combined application of IRMS and GC-MS to differentiate partial acylglycerols are still limited.…”
Section: Introductionmentioning
confidence: 99%